ðŽMc â€“functions and ð‘µMc-functions - Humadi, Nadia Kadum; Ali, Haider Jebur (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, we presented new types of Mc-function by using ðœ”-open and ð‘-open sets some of them are weaker than Mc-function and some are stronger, which are ðœ”Mc-function, Mðœ”c-function, ðœ”Mðœ”c-function, ð‘Mc-function, Mð‘c-function and ð‘Mð‘c-function, also we submitted new kinds of continuous functions and compact functions and we illustrated the relationships between these types. The purpose of this paper is to expand the study of Mcfunction and to get results that we need to find the relationship with the types that have been introduced.